2012
DOI: 10.1109/tnsre.2012.2189585
|View full text |Cite
|
Sign up to set email alerts
|

Towards a Biomarker of Motor Adaptation: Integration of Kinematic and Neural Factors

Abstract: We propose an experimental protocol for the integrated study of motor adaptation during target-based movements. We investigated how motor adaptation affects both cerebral activity and motor performance during the preparation and execution of a pointing task, under different conditions of external perturbation. Electroencephalography (EEG) and movement analysis were simultaneously recorded from 16 healthy subjects enrolled in the study. EEG signal was preprocessed by means of independent component analysis and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 50 publications
2
8
0
Order By: Relevance
“…This interpretation is consistent with Molteni et al [15], that showed in their research that the statement that neural effort did not decrease trough conditions, but rather supported behavioral improvement.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…This interpretation is consistent with Molteni et al [15], that showed in their research that the statement that neural effort did not decrease trough conditions, but rather supported behavioral improvement.…”
Section: Discussionsupporting
confidence: 92%
“…It could be an indication of an increasing neural effort to refine the strategy, despite the improvement in behavioral performance. Therefore, this interpretation would lead to conclude that the neural control effort did not decrease through learning, but rather supported behavioral improvement [15]. These ideas can be considered in the design and applications of rehabilitation robots and exoskeletons.…”
Section: Introductionmentioning
confidence: 78%
See 2 more Smart Citations
“…To achieve optimal results -this means the rapid learning of motor skills at a minimum risk of injury or other negative side effects in Alpine skiing -the process has to be appropriately structured (Molteni et al, 2012). The principle of progressivity in speed and complexity of movement is an important didactic principle according to which the individual is guided until they carry out a skiing element optimally (Winter, 2009).…”
Section: Introductionmentioning
confidence: 99%